DIGITAL MARKETING ASSISTANCE TO INCREASE THE TURNOVER AND IMAGE OF MSMEs THROUGH FOOD PHOTOGRAPHY AND SOCMED - Andhatu Achsa; Dian Marlina Verawati; Dinar Melani Hutajulu (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2023)
This program was implemented with the aim of helping MSMEs entrepreneurs in Balesari Village, Windusari District, Magelang Regency, Central Java to increasing business turnover and expanding the market for these MSMEs products. The form of this activity was mentoring activities with lecture methods, tutorials, and discussions on digital marketing topics, food photography, attractive photo visual strategies and the use of social media as a promotional tool. As a result of this activity, MSMEs entrepreneurs gain knowledge and information about the world of digital marketing, social media accounts for selling, attractive product photos created by MSMEs entrepreneurs, promotional tricks and interesting sentences and attractive titles for promotion. MSMEs entrepreneurs have shown an increase in understanding about digital marketing and the products they produce for digital marketing. With the implementation of this activity, it is hoped that Balesari Village MSMEs entrepreneurs can be more consistent in carrying out business and promotional activities in the digital world so that they can support increased turnover and market expansion of Balesari Village MSME products. Keywords: digital marketing, increased turnover, MSMEs